ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION PADA PENGGUNA SMARTPHONE DI BATAM - Lily Purwianti; Tommy Ricarto (Jurnal Manajemen Maranatha, 2018)
The focus of this study was to analyze the factors direct impact on purchase intention of smartphone’s users in Batam. Sample was taken from 400 smartphone’s user most crowded reseller shop in Batam (Nagoya hill and Lucky Plaza). The research data that has been collected and analyzed using the program statistical package for social sciences (smart pls). Results from this study showed a significant and no significant effect of independent on the dependent variable. First, brand awareness has a significant effect on perceived quality. Second, brand awareness and perceived quality has a significant effect on brand loyalty. Thirth, perceived quality, brand loyalty and brand awareness and brand association has a significant effect on purchase intention. Keywords: Brand awareness, perceived quality, brand loyalty, brand association and purchase intention